KONTRIBUSI SISTEM MANAJEMEN PESERTA DIDIK TERHADAP PRESTASI NON-AKADEMIK DI SD NEGERI 1 BANJARNEGERI KABUPATEN TANGGAMUS - Asep, Asep; Setyo Erni Puspita; Herlina, Herlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the contribution of the student management system to non-academic achievement at SD Negeri 1 Banjarnegeri, Tanggamus District, particularly in the Festival Lomba Seni dan Sastra Siswa Nasional (FLS3N). The school’s achievements in story writing, storytelling, and expressive drawing indicate the presence of an effective and well-structured student management system. This research employed a descriptive qualitative approach with a case study design. Informants included the principal, the vice principal for student affairs, FLS3N coaches, award-winning students, and parents selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis, and examined using the Miles, Huberman, and Saldana model consisting of data reduction, data display, and conclusion drawing. The findings show that structured planning, clear organizational roles, intensive coaching, adequate supporting facilities, and continuous monitoring and evaluation play a crucial role in improving non-academic coaching quality. The student management system significantly contributes to students’ achievements, as evidenced by their awards at the sub-district and district levels in three FLS3N competition categories. The study concludes that a comprehensive and consistent student management system is effective in optimizing students’ potential and enhancing non-academic achievements in primary schools. Keywords: student management, non-academic achievement, FLS3N, extracurricular coaching